The interactive whiteboard in primary school: a case study of a brazilian district school - Esteves, Rodolfo Fernandes [UNESP]; Fiscarelli, Silvio Henrique [UNESP]; Bizelli, Jose Luis [UNESP] (My University, 2015)
Interactive whiteboards (IWB) consist of a set of technological equipment organized in order to fulfill a specific task, enabling the development of didactic activities. Because they are associated to computers’ potentiality, interactive whiteboards can provide bigger interactivity between: teacher and students, students and content, and among students. This work’s main objective is to present some of the results yielded from a research related to the way students perceive interactive whiteboards in the classroom. In order to analyze the IWB usage dynamics, some educational applications in the field of mathematics were applied in the 3rd grade of elementary school. Aside from observation, video recordings were made and students were interviewed about the interactive whiteboard, in order to understand how these students observe and engage with the technological tool. IWB do not transform classroom’s reality by themselves, however, their physical presence and usage amount to external reinforcement can change student’s behavior positively.
Keywords: Public Education; Interactive Whiteboard; ICT